2017
DOI: 10.1097/mao.0000000000001355
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Bleeding and the Risk of Residual Cholesteatoma: A Multivariate Analysis

Abstract: Impaired surgical field clarity from intraoperative bleeding is associated with increased risk of residual cholesteatoma in surgery for meso/epitympanic cholesteatoma. These findings are of particular significance for endoscopic ear surgery in which management of bleeding can be more difficult and support the use of techniques, such as hypotensive general anesthesia, that minimize surgical site bleeding and improve surgical field visualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…On the other hand, the hereby investigated model lacks bleeding, which is of course an important issue in the operating room. The one-handed surgical technique in EES requires decent knowledge and skills in managing the bleeding [18, 19], which are different from the microscopic technique and may impede with the learning curve during clinical application. However, it is important to stress, that technical as well as procedural differences should not be confounded with learning curves for young surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the hereby investigated model lacks bleeding, which is of course an important issue in the operating room. The one-handed surgical technique in EES requires decent knowledge and skills in managing the bleeding [18, 19], which are different from the microscopic technique and may impede with the learning curve during clinical application. However, it is important to stress, that technical as well as procedural differences should not be confounded with learning curves for young surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…11 This especially holds true for single-handed endoscopic surgery, which may put critical structures at risk and also increase the chance of leaving behind residual disease. 12 However, with a good local infiltration, intraoperative use of adrenaline-soaked cotton balls and appropriate suction instruments, a clear working field can be achieved in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…The figures of residual disease detected in our study concur with those by figures reported by other workers, namely El Meselaty, 7 Presutti, 8 Ayubi, 9 Ayache, 10 Elfeky, 11 le Nobel. 13 Our study had a few limitations. Firstly, it was a relatively small study sample of 42 patients.…”
Section: Discussionmentioning
confidence: 94%